2007
DOI: 10.1562/0031-8655(2001)0740226gofrbe2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Free Radicals by Emodic Acid and its [d-Lys6]GnRH-conjugate¶

Abstract: In an attempt to develop an efficient chemotherapeutic agent targeted at malignant cells that express receptors to gonadotropin releasing hormone (GnRH) we coupled [D-Lys 6 ]GnRH covalently to an emodin derivative, i.e. emodic acid (Emo) to yield [D-Lys 6 (Emo)]GnRH. Emodin is a naturally occurring anthraquinone which is widely used as a laxative and has other versatile biological activities. Physico-chemical studies employing electron paramagnetic resonance and electrochemistry of the conjugate as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Thus, when EO reaches the cell it can undergo oxidation or reduction reactions. As mentioned previously, the reduction of EO initially yields its semiquinone, which can generate the superoxide anion (O 2 .-) in the presence of oxygen due to electron transfer from the semiquinone to molecular oxygen (Rahimipour et al, 2001). Almost any oxidation of phenolics in the gut can generate O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, when EO reaches the cell it can undergo oxidation or reduction reactions. As mentioned previously, the reduction of EO initially yields its semiquinone, which can generate the superoxide anion (O 2 .-) in the presence of oxygen due to electron transfer from the semiquinone to molecular oxygen (Rahimipour et al, 2001). Almost any oxidation of phenolics in the gut can generate O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…By interacting with enzymes, transporters, channels, and receptors, EO has access to multiple cellular targets and can interfere with many pathways, which is a common feature of many plant phenolics (Mueller et al, 1998;Srinivas et al, 2007 and references therein;Teng et al, 2012;Dong et al, 2016). As a quinone, EO has a marked oxidative impact on the cellular redox status and on the generation of reactive oxygen species (ROS) (Rahimipour et al, 2001;Srinivas et al, 2007;Mecklenburg et al, 2009;Martín-Cordero et al, 2012;Qu et al, 2013;Liu et al, 2015;Lennicke et al, 2016). EO can be reduced to its semiquinone, which in the presence of molecular oxygen generates the superoxide anion (O 2 al., 2009;Lennicke et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous workers have shown that electron paramagnetic resonance and electrochemical studies of AQ such as emodin could be easily reduced to semiquinone form and in the presence of oxygen and the semiquinones generate ROS, mainly superoxide. 30 Intracellular increase in ROS often leads to apoptosis, which is considered to be the mechanism of action of cytotoxicity in cancer cells mediated by AQs. 31 Anti-inflammatory activity was observed in AQf-treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of toxicity of 1,8-dihydroxyanthraquinones, such as emodin, likely involves redox cycling between the quinone and the semiquinone radical generating reactive oxygen species (ROS) resulting in lipid peroxidation, protein damage, and DNA oxidation ( Figure 2) (26,29,30). For example, treatment of Reuber hepatoma and fibroblast Balb/3T3 cells with various anthraquinones resulted in the formation of 8-oxo-dG (26).…”
Section: Cascara Sagradamentioning
confidence: 99%